The Role of Merdeka Belajar Kampus Merdeka (MBKM) Program on Students' Soft Skills: An Observational Study of Students in Jambi City, Indonesia - Saputri, Effri Dwiyana; Novia Sri Dwijayanti; Arpizal (Arkus, 2024)
The Merdeka Belajar Kampus Merdeka (MBKM) program was launched by the Indonesian government with the aim of improving the quality of higher education and preparing graduates who are competent in the world of work. One important aspect that is expected to be improved through this program is student soft skills. This research aims to examine in depth the role of MBKM in the development of student soft skills in Jambi City, Indonesia. This research used an observational approach involving 350 students from various universities in Jambi City who participated in the MBKM program. Data was collected through participant observation, in-depth interviews, and questionnaires. Data analysis was carried out qualitatively and quantitatively to explore a comprehensive understanding of the impact of MBKM on student soft skills. The research results show that MBKM has a significant role in improving the soft skills of students in Jambi City. Participation in various MBKM activities, such as internships, humanitarian projects, and student exchanges, provides opportunities for students to develop communication skills, leadership, teamwork, problem-solving, and creativity. Apart from that, MBKM also helps students increase their self-confidence, independence, and ability to adapt to new environments. The MBKM program has proven effective in improving the soft skills of students in Jambi City. These findings provide empirical evidence that supports the importance of the MBKM program in preparing graduates who not only have academic competencies, but also the soft skills needed in the world of work. The implications of this research can be used as a basis for developing higher education policies that are more effective in improving the quality of graduates.